274 Use of DHS For Fixation of Unstable Hip Fractures – Are Outcomes Any Different from Nails?. (12th October 2021) - Arora, N
Abstract: Aim: To determine if the outcomes and rate of complications differ based on choice of implant for unstable hip fractures. Method: Retrospective analysis of 105 hip fractures operated in 2015 + 2016 with AO classification A2.2. A2.3 or A3. These were divided into 2 groups depending on whether DHS/Plate implant was selected (n = 86) or Nail implant was used (n = 19). Any complications occurring in their subsequent management or performance of any revision procedures were recorded. 6-month mortality rate was also calculated for both groups. Results: When A2 and A3 fractures were assessed together the rate of acute complications was similar in both groups. 21% for nails and 19% for plates. The rate of delayed complications was not significantly different either, 16% for nails and 10% for plates. Revision procedures were more common where nails had been used (16%) compared to only 6% of plate fixations. Mortality rates were identical. When looking at A3 fractures in isolation, the rate of delayed complications is significantly higher when plates are used (24%) compared to 12% when nails are selected. Conclusions: We did not identify any significant difference in acute complications including bleeding and infection based on choice of implant. This goes against common arguments raised against use of nails. Successful use of DHS fixation in unstable A2 hip fractures is possible, as evidenced by similar rates of delayed complications. Revisions were higher when nail was selected. It is however noted that for reverse oblique fractures nails perform demonstrably better, with half as frequent delayed complications and revisions.